2018
DOI: 10.1039/c8nj00357b
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Schiff base compounds and their coordination complexes with the drug cisplatin

Abstract: There is a complex interplay between the structural and other physicochemical properties of new compounds and the molecules in living organisms. To understand the mechanism of the interactions at the molecular level, the correlations between the selected properties and their biological responses have to be examined. With this aim, in this paper, density functional theory (DFT) and LMP2 calculations were carried out for the 2-acetylpyridine-aminoguanidine ligand, L, and its copper(II) complexes containing diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 80 publications
0
13
0
Order By: Relevance
“…s.u., 2) the molecular weight within range 180–500 g mol −1 , 3) the number of atoms from 20–70. Further, the MR value is responsible for the lipophilicity, binding property, polarizability and dispersitivity of the molecular system ( Magyari et al, 2018 ). The calculated values of MR for CAF, monomer and dimer model of cocrystal are 30.26 e.…”
Section: Resultsmentioning
confidence: 99%
“…s.u., 2) the molecular weight within range 180–500 g mol −1 , 3) the number of atoms from 20–70. Further, the MR value is responsible for the lipophilicity, binding property, polarizability and dispersitivity of the molecular system ( Magyari et al, 2018 ). The calculated values of MR for CAF, monomer and dimer model of cocrystal are 30.26 e.…”
Section: Resultsmentioning
confidence: 99%
“…A checkerboard microplate method was applied to study the effect of drug interactions between the tested compounds and the chemotherapeutic drug, doxorubicin (Teva Pharmaceuticals), thus to determine the combination index (CI) for the compounds (Magyari et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…Numerous Schiff-bases and their derivatives have been reported to possess promising biological properties and several review articles have been published in the past few years. [37][38][39][40][41][42][43][44] Recently, review articles regarding the biological applications of macrocyclic Schiff-base ligands and their metal complexes have been published. [32,34] However, no comprehensive review has been published recently on the biological properties of metallic derivatives of acyclic Schiff-base ligands.…”
Section: Scope Of This Reviewmentioning
confidence: 99%
“…[34] Macrocyclic Schiff-bases [32][33][34] have found important applications in macrocyclic and supramolecular chemistry, and various heterocyclic Schiff-bases and their derivatives play crucial roles in medicinal chemistry. [35,36] Furthermore, depend-to their structural flexibility, they can be synthetically modified and fine-tuned for specific biological applications and many metallic [3,15,17,18,[37][38][39] and non-metallic [15,[40][41][42][43][44] derivatives of Schiffbases are being researched extensively to develop new compounds with desired biological properties. The imine or azomethine group in structure-activity relationship (SAR) studies of Schiff-bases have shown the considerable chemical and biological importance for the lone pair of electrons in the sp 2 -hybridized orbital of nitrogen atom of the À C=NÀ group.…”
Section: Introduction 1schiff-bases and Their Different Derivativesmentioning
confidence: 99%
See 1 more Smart Citation